Peritoneal Tuberculosis in Chronic Ambulatory Peritoneal Dialysis: A Case Report - Plaza-Mosquera, Stephanie Del Valle (2026)
Peritonitis was the main complication of peritoneal dialysis, most commonly caused by coagulase-negative Staphylococcus, Staphylococcus aureus, Streptococcus spp., and Gram-negative bacilli, whereas unusual pathogens such as fungi or Mycobacterium tuberculosis occurred less frequently. We presented the case of a patient undergoing chronic ambulatory peritoneal dialysis who developed tuberculous peritonitis, with persistently negative peritoneal fluid cultures and an unfavorable clinical course. The presentation was atypical and prolonged, underscoring the need to consider alternative diagnoses when the clinical evolution was not typical and the etiology remained unclear. This case illustrated the importance of a meticulous clinical evaluation, the timely use of complementary diagnostic tools, and maintaining a high index of suspicion in patients who do not respond to conventional management. In doing so, it aimed to contribute to the existing literature and reinforce clinical vigilance regarding unusual complications in peritoneal dialysis.